A kind of synthesis process of iron stearate
Through the modification of organic solvents, improve the solubility of lipidic acid and viscosity of the reaction system, form a smaller and uniform hard fatty acid iron particles, solve the problem of insufficient solid iron and moisture absorption, significantly improves the product of the product Stability and purity reduce the cost of storage and production.
Patent Information
- Application Number
- CN202411244602.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing iron stearate easily absorbs moisture in the air during storage and use, resulting in a degradation of performance and affecting the use effect.
Through the modified treatment of organic solvents, the use of ethylene glycol, propylene glycol, and glycerin as a modifier to improve the solubility and viscosity of the response system in the reaction system Hard -lipide iron particles.
A significant reduction of the moisture absorption performance of the hard fatty acid iron, reducing the block and performance changes caused by hygroscopic absorption, improving the stability and purity of the product, and reducing the difficulty of storage and production costs.
Smart Images

Figure CN118754810B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of iron stearate production, in particular to a synthesis process of iron stearate. Background Art
[0002] As an indispensable industrial additive, the core value of iron stearate is that it significantly promotes the innovation and development of the field of photodegradable polyolefin film materials. This type of film is widely used in modern agriculture, packaging industry and construction, including but not limited to environmentally friendly agricultural mulch film, high-efficiency agricultural film, degradable shopping bags, environmentally friendly packaging bags, construction packaging film and environmentally friendly garbage bags, etc., which not only provides convenience and protection for modern society, but also actively responds to the urgent global demand for environmental protection.
[0003] As a key photosensitive catalyst, iron stearate plays a vital role in the photodegradation process. It can efficiently absorb light energy of specific wavelengths in sunlight and convert it into chemical energy, thereby triggering and accelerating the breakage and recombination of polyolefin molecular chains, and ultimately achieving the natural degradation of the film. This process not only effectively reduces the long-term accumulation of plastic waste in the natural environment, but also reduces the potential harm of traditional plastic waste to soil, water bodies and ecosystems, and has immeasurable value in maintaining ecological balance and promoting sustainable development.
[0004] Announcement No. CN100391927C discloses a method for synthesizing iron stearate. The method adds stearic acid to a 0.5%-3% sodium hydroxide solution, reacts to pH 9-10, and obtains a sodium stearate solution; then the sodium stearate solution is cooled to 60-80°C, and a 1%-10% soluble iron salt solution at 50-70°C is added thereto to generate an orange-yellow iron stearate precipitate; finally, the iron stearate powder is obtained by filtering, washing, and drying. The present invention improves the process of synthesizing iron stearate by the saponification-double decomposition method, and stearic acid can be completely converted in the saponification stage, and the product does not contain stearic acid: the iron stearate generated in the double decomposition reaction stage can be precipitated in the form of a precipitate, and the precipitation washing operation is very convenient. The obtained iron stearate product has high purity, a narrow melting point range, an iron content close to the theoretical value, and a yield of 93.8%-95.1%.
[0005] The existing iron stearate needs to maintain a certain stability during storage and use to ensure that its photosensitivity is not affected. However, since iron stearate is hygroscopic, it easily absorbs moisture in the air, resulting in a decrease in performance and affecting its use effect. Therefore, it is of great significance to develop a synthesis process for iron stearate that can reduce hygroscopicity. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a synthesis process for iron stearate, which can reduce the hygroscopicity of the generated iron stearate powder.
[0007] To achieve the above object, the present invention provides the following technical solution: a synthesis process of iron stearate, comprising the following steps:
[0008] S1, preparing an organic solvent, and modifying the organic solvent by adding a modifier to obtain a modified organic solvent, wherein the modifier includes ethylene glycol, propylene glycol and glycerol, and the organic solvent is ethanol;
[0009] S2, dissolving stearic acid in a modified organic solvent to obtain a stearic acid solution;
[0010] S3, preparing a soluble iron salt solution;
[0011] S4, mixing the stearic acid solution with the soluble iron salt solution, reacting to generate iron stearate precipitate;
[0012] S5. Filter, wash and dry the iron stearate precipitate to obtain an iron stearate product.
[0013] Preferably, the volume percentages of ethylene glycol, propylene glycol and glycerol are 10%, 20% and 5% respectively.
[0014] Preferably, the molar ratio of stearic acid to soluble iron salt is 7:1.
[0015] Preferably, the soluble iron salt is ferrous sulfate or ferric chloride.
[0016] Preferably, the reaction temperature is 60-80° C. and the reaction time is 1-2 hours.
[0017] Preferably, the filtration is performed by vacuum filtration and the washing is performed by ethanol.
[0018] Preferably, the drying temperature is 40-60°C and the drying time is 4-6 hours.
[0019] Compared with the prior art, the present invention provides a synthesis process of iron stearate, which has the following beneficial effects: by modifying the organic solvent, the reaction rate and the particle size of the product are controlled, and higher viscosity helps to form finer and more uniform iron stearate particles. Due to the improvement of the uniformity and surface properties of the particles, the hygroscopic properties of the synthesized iron stearate can be significantly reduced, and the problems of agglomeration and performance changes caused by moisture absorption are reduced, thereby reducing the difficulty of storing iron stearate, avoiding the degradation of performance of iron stearate due to excessive absorption of moisture in the air, and damaging the purity and use performance of the product;
[0020] Secondly, the invention improves the completeness of the raw material reaction in the entire reaction process, and the iron content in the synthesized iron stearate is significantly improved, so that higher purity iron stearate can be obtained, and the more complete the reaction, the higher the yield of iron stearate, which reduces the loss rate of production raw materials and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The figure is a flow chart of a synthesis process of iron stearate. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In the present invention, the solubility is improved: ethylene glycol and propylene glycol, as polar organic solvents, can improve the solubility of stearic acid, so that stearic acid can be more evenly dispersed in the reaction solution. This helps to increase the contact area between stearic acid and iron salt, and promotes the reaction.
[0024] Glycerol: Glycerol is also a polar solvent that can increase the viscosity of the solution and further improve the solubility of stearic acid in the reaction solution;
[0025] Since glycerol has a higher viscosity, it can provide better particle stability during the reaction process, prevent the generated iron stearate particles from aggregating and precipitating prematurely, and ensure the particle size uniformity and dispersibility of the product.
[0026] Reaction environment adjustment: Ethylene glycol: Ethylene glycol has a higher boiling point and lower vapor pressure. When reacting at a higher temperature, it can provide a stable reaction environment and reduce solvent volatilization losses.
[0027] Propylene glycol and glycerol: These components can adjust the polarity and viscosity of the reaction system, thereby controlling the reaction rate and the particle size of the product. Higher viscosity helps to form smaller and more uniform iron stearate particles.
[0028] Iron content determination: The iron content in the product was determined using an ICPQ-100 plasma emission spectrometer from Shimadzu Corporation of Japan;
[0029] Theoretically, the iron content of iron stearate should be 8.96%. However, there is often a certain amount of impurities in the production process. Therefore, the theoretical value is often difficult to achieve, which will also affect the degradation performance of the film produced subsequently using the iron stearate.
[0030] It should be noted that the determination of hygroscopicity is to measure the ability of a sample to absorb water over a period of time under specific environmental conditions. The specific steps are as follows:
[0031] Sample preparation:
[0032] Weigh a certain amount of sample (e.g. 20 g) and place it in a desiccator to cool to room temperature;
[0033] Environmental Control:
[0034] The temperature was set to 25 °C and the relative humidity to 75% in a constant temperature and humidity chamber.
[0035] Place the cooled sample in a constant temperature and humidity chamber for a certain period of time (usually 24 hours);
[0036] Determination of moisture absorption:
[0037] Take out the sample from the constant temperature and humidity chamber and weigh its mass quickly.
[0038] Calculate the moisture absorption and calculate the moisture absorption performance according to the following formula:
[0039]
[0040] in, is the mass of the sample after moisture absorption, is the mass of the sample before moisture absorption.
[0041] Test equipment: Constant temperature and humidity chamber: model TH-8000, analytical balance: model Sartorius CP224S.
[0042] The determination of the yield of iron stearate is calculated by the ratio of the actual yield of iron stearate generated by the reaction to the theoretical yield. The specific steps are as follows:
[0043] Theoretical yield calculation:
[0044] According to the reaction equation, calculate the theoretical mass of iron stearate that should be generated in the reaction;
[0045] Assuming that stearic acid and iron salt react completely, calculate the theoretical yield of iron stearate based on the molar ratio (7:1);
[0046] Actual yield determination:
[0047] Filtering, washing and drying the iron stearate precipitate generated by the reaction;
[0048] Weigh the mass of the dried iron stearate;
[0049] Yield calculation: The yield of iron stearate was calculated according to the following formula:
[0050]
[0051] in, is the actual mass of iron stearate obtained, This is the theoretical mass of iron stearate that should be obtained.
[0052] Testing equipment: analytical balance: model Sartorius CP224S, vacuum filter: model Büchi V-700, drying oven: model Memmert UF75;
[0053] By means of the above method and equipment, the hygroscopicity and yield of iron stearate can be accurately determined, ensuring the reliability and repeatability of the experimental data.
[0054] Embodiment 1:
[0055] A synthetic process for iron stearate, specifically comprising the following steps:
[0056] S1. Heat 100 mL of ethanol to 55°C;
[0057] S2, add 10 mL of ethylene glycol, 20 mL of propylene glycol and 5 mL of glycerol to ethanol, stir evenly to obtain a modified organic solvent;
[0058] S3, dissolving 10 g of stearic acid in a modified organic solvent to obtain a stearic acid solution;
[0059] S4, prepare 100 mL of 0.05 mol / L ferrous sulfate solution;
[0060] S5, mixing the stearic acid solution with the ferrous sulfate solution, and reacting at 60°C for 2 hours;
[0061] S6, filtering the precipitate and washing with ethanol;
[0062] S7, drying temperature 40 ℃, drying time 6 hours, to obtain the iron stearate product.
[0063] Embodiment 2:
[0064] A synthetic process for iron stearate, specifically comprising the following steps:
[0065] S1. Heat 100 mL of ethanol to 55°C;
[0066] S2, add 12 mL of ethylene glycol, 25 mL of propylene glycol and 7 mL of glycerol to ethanol, stir evenly to obtain a modified organic solvent;
[0067] S3, dissolving 10 g of stearic acid in a modified organic solvent to obtain a stearic acid solution;
[0068] S4, prepare 100 mL of 0.05 mol / L ferrous sulfate solution;
[0069] S5, mixing the stearic acid solution with the ferrous sulfate solution, and reacting at 70°C for 1.5 hours;
[0070] S6, filtering the precipitate and washing with ethanol;
[0071] S7, drying temperature 50 ℃, drying time 5 hours, to obtain the iron stearate product.
[0072] Embodiment three:
[0073] A synthetic process for iron stearate, specifically comprising the following steps:
[0074] S1. Heat 100 mL of ethanol to 55°C;
[0075] S2, add 15 mL of ethylene glycol, 30 mL of propylene glycol and 10 mL of glycerol to ethanol, stir evenly to obtain a modified organic solvent;
[0076] S3, dissolving 10 g of stearic acid in a modified organic solvent to obtain a stearic acid solution;
[0077] S4, prepare 100 mL of 0.05 mol / L ferrous sulfate solution;
[0078] S5, mixing the stearic acid solution with the ferrous sulfate solution, and reacting at 80°C for 1 hour;
[0079] S6, filtering the precipitate and washing with ethanol;
[0080] S7, drying temperature 60 ℃, drying time 4 hours, to obtain the iron stearate product.
[0081] Comparative Example 1:
[0082] S1. Heat 100 mL of ethanol to 55°C;
[0083] S2, dissolving 10 g of stearic acid in ethanol to obtain a stearic acid solution;
[0084] S3, prepare 100 mL of 0.05 mol / L ferrous sulfate solution;
[0085] S4, mixing the stearic acid solution with the ferrous sulfate solution, and reacting at 60°C for 2 hours;
[0086] S5, filtering the precipitate and washing it with ethanol;
[0087] S6, drying temperature 40 ℃, drying time 6 hours, to obtain the iron stearate product.
[0088] Comparative Example 2:
[0089] S1. Heat 100 mL of ethanol to 55°C;
[0090] S2, dissolving 10 g of stearic acid in ethanol to obtain a stearic acid solution;
[0091] S3, prepare 100 mL of 0.05 mol / L ferrous sulfate solution;
[0092] S4, mixing the stearic acid solution with the ferrous sulfate solution, and reacting at 80°C for 1 hour;
[0093] S5, filtering the precipitate and washing it with ethanol;
[0094] S6, drying temperature 60 ℃, drying time 4 hours, to obtain the iron stearate product.
[0095] In Experiment 1, the five groups of iron stearate powder products in Examples 1, 2, 3 and Comparative Examples 1 and 2 were tested for iron content. The higher the iron content test percentage value, the higher the purity of the obtained iron stearate, and vice versa.
[0096] Table 1. Test results of iron content in iron stearate
[0097]
[0098] Based on the above data, the iron content of the iron stearate in Examples 1, 2 and 3 is significantly higher than that in Comparative Examples 1 and 2, and a high iron content means that the purity of the prepared iron stearate is higher. Therefore, the modifier in the preparation process of the present invention can significantly improve the conversion rate of the iron element in the production process and the sufficiency of the reaction of the raw materials during the reaction.
[0099] Experiment 1: The five groups of iron stearate powder products in Examples 1, 2, 3 and Comparative Examples 1 and 2 were tested for the iron stearate yield and hygroscopic performance. The higher the percentage value of the iron stearate yield, the higher the corresponding conversion yield, and vice versa. The higher the percentage value of the hygroscopic performance value, the higher the hygroscopic capacity, and vice versa. At the same time, a sample of iron stearate synthesized by announcement number CN100391927C was obtained (referred to as: comparison sample), and the hygroscopic performance of the comparison sample was tested.
[0100] Table 2. Test results of iron stearate yield and hygroscopicity
[0101]
[0102] Based on the above data, the yield of iron stearate in Examples 1, 2 and 3 is significantly higher than that in Comparative Examples 1 and 2, and the yield of iron stearate represents the raw material conversion rate in the reaction process. Therefore, the synthesis process of the present invention can significantly improve the conversion efficiency of raw materials in the reaction process by adding a modifier, thereby achieving the purpose of reducing production costs. At the same time, the addition of a modifier can significantly reduce the hygroscopicity of iron stearate after synthesis, thereby reducing the difficulty in its storage process, avoiding the degradation of performance caused by iron stearate due to excessive absorption of moisture in the air, and destroying the purity and performance of the product.
[0103] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0104] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A process for synthesizing iron stearate, characterized in that: The specific steps include: S1. preparing an organic solvent, and modifying the organic solvent by adding a modifier to obtain a modified organic solvent, wherein the modifier comprises ethylene glycol, propylene glycol and glycerol, and the volume percentages of ethylene glycol, propylene glycol and glycerol relative to the organic solvent are 10%-15%, 20%-30% and 5%-10%, respectively, and the organic solvent is ethanol; S2, dissolving stearic acid in a modified organic solvent to obtain a stearic acid solution; S3, preparing a soluble iron salt solution, wherein the soluble iron salt is ferrous sulfate or ferric chloride; S4, mixing the stearic acid solution with the soluble iron salt solution, reacting to generate iron stearate precipitate; S5. Filter, wash and dry the iron stearate precipitate to obtain an iron stearate product.
2. A process for synthesizing ferrous stearate according to claim 1, characterized in that: The molar ratio of the stearic acid to the soluble iron salt is 7:
1.
3. A process for synthesizing ferrous stearate according to claim 1, characterized in that: The reaction temperature is 60-80°C and the reaction time is 1-2 hours.
4. A process for synthesizing ferrous stearate according to claim 1, characterized in that: The filtration is performed by vacuum filtration, and the washing is performed by ethanol.
5. A process for synthesizing ferrous stearate according to claim 1, characterized in that: The drying temperature is 40-60°C and the drying time is 4-6 hours.
Citation Information
Patent Citations
Method for synthesizing ferrous stearate
CN100391927C
Battery grade nano ferrous oxalate, its preparation method and application
CN102344356A